Islanding Detection Technology of Grid-connected PV Inverter - ZHANG Honghao; ZHU Shiwu; WU Hengliang; TANG Zhou (Kongzhi Yu Xinxi Jishu)
It is indispensable to detect islanding in PV grid-connected generation. However, it is difficult to detect islanding in the case of power balance between the output of inverter and the load power, as the load resonant frequency is closing to the grid frequency. Thus the islanding detection method was researched based on the positive feedback of reactive current and frequency, and the accurate range of coefficient of positive feedback was detruded. This method can not only detect islanding quickly, but has no negative effect on the power quality of inverter output. Theoretical derivation, Matlab simulation and product certification experiment in CGC show that the proposed method is valid and reliable.